Here's the question you clicked on:
Kelumptus
integral(-1/(x ln x))dx = Integral(1/y) dy
integral(-1/(x ln x))dx = Integral(1/y) dy = ln(ln(x)) = ln(y) +c = ln(x) = y +c Is this correct?
u missed a *minus* sign integral(-1/(x ln x))dx = Integral(1/y) dy =- ln(ln(x)) = ln(y) +c =- ln(x) = y +c
oh... hehe apart from that sorry =)
yes, apart from that its absolutely correct.
because the site i am reading has "y = c ln x" And that doesn't seem right...?
no, i don't think thats correct.
He even misses the minus sign also. Thanks for confirming this for me.